Table for two: The effects of familiarity, sex and gender on food choice in imaginary dining scenarios. (1st December 2015) - Dibb-Smith, Amanda; Brindal, Emily
Abstract: Introduction: Existing research suggests that eating behaviours may be used to modify self-presentation and that process may be different for women compared to men. We aimed to assess how people make different food choices in situations of varying self-presentation demand. Method: Via an online survey, eligible participants (n = 216; 64% female: not on a restrictive diet or severely obese/underweight) were allocated to one of four experimental conditions manipulating the familiarity (close friend v acquaintance) and sex of an eating companion (same v opposite sex). All participants were asked to imagine they were eating out with one of the manipulated companions, and were presented with a menu and asked to order items. Menu choices were used to calculate the total kilojoules ordered, percentage of kilojoules from fats and number of low-fat options selected. To assess differences in impression management, participants completed the Paulhus Deception scale. Results: Despite successful manipulation checks, analyses of covariance (controlling for levels of hunger) revealed no main or interaction effects for familiarity and sex composition for any of the menu choice outcomes assessed. Impression management scores differed for sex composition (main effect only) with participants who imagined dining with someone of the same gender ( M  = 2.05, SE  = 0.90) having higher impression management scores than those imagining dining with an opposite sex companion ( M  = 1.27, SE  = 0.83). Conclusion: We found preliminary support that gender composition could alter impression management demands but this did not translate to differences in food choice. Highlights: An experimental study on impression management and food choice was performed. Participant and companion sex, gender and familiarity are relevant factors. Same-sex eating scenarios increased the desire to manage impressions. Masculine individuals trended towards selecting more energy-dense foods. Multiple social factors drive impression management and food selection.